2017
DOI: 10.1002/ldr.2657
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Long‐Term Soil Erosion in a Mountain Vineyard, Aosta Valley (NW Italy)

Abstract: In the mountain region of Aosta Valley, NW Italy, grapevine were, in the past, traditionally grown on terraces supported by dry stone walls. Since the 1960s, terrace systems were gradually abandoned in favour of an up and down slope row orientation. Tillage and chemical weeding are common soil management techniques adopted in vineyards with high slope gradient, to maintain bare soil. Both techniques expose, to varying degrees, the soil to degradation, favouring runoff and soil losses. Although many studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 63 publications
(104 reference statements)
2
31
0
4
Order By: Relevance
“…In both maps, we detected that the highest depleted areas are located in the upper part of the transect (orange-red colours) reaching values higher than 20 cm, and in the areas close to the vine rows (orange-yellow colours). Our results corroborate with other researchers who found these parts to be the most eroded areas due to wheel or chain traffic effects [40,41] as a result of gravitational processes [42]. Conversely, the areas with the lowest soil depletion are situated in the middle part of the plot, unaffected by the tractor impacts and also non-compacted [43].…”
Section: Soil Surface Level Assessment and Soil Mobilisation Ratessupporting
confidence: 92%
See 1 more Smart Citation
“…In both maps, we detected that the highest depleted areas are located in the upper part of the transect (orange-red colours) reaching values higher than 20 cm, and in the areas close to the vine rows (orange-yellow colours). Our results corroborate with other researchers who found these parts to be the most eroded areas due to wheel or chain traffic effects [40,41] as a result of gravitational processes [42]. Conversely, the areas with the lowest soil depletion are situated in the middle part of the plot, unaffected by the tractor impacts and also non-compacted [43].…”
Section: Soil Surface Level Assessment and Soil Mobilisation Ratessupporting
confidence: 92%
“…Considering that our results correspond to a small plot using a photogrammetric technique, the registered soil erosion rates are not significantly different from those reported in other studies in Germany. Using empirical methods such as RUSLE (Revised Universal Soil Loss Equation), References [46,47] processes [42]. Conversely, the areas with the lowest soil depletion are situated in the middle part of the plot, unaffected by the tractor impacts and also non-compacted [43].…”
Section: Soil Surface Level Assessment and Soil Mobilisation Ratesmentioning
confidence: 99%
“…This method allows estimation of soil depletion and accumulation at temporal scales sufficiently long to assess the cumulative effects of agricultural practice impacts, but also to demonstrate the spatial mobilization of sediment detachment, transport and deposition under the natural conditions (Chevigny et al ., ; Biddoccu et al ., ). However, in addition to acquiring much more accurate erosion rates with ISUM, we also found that the maps created with the ISUM technique can be used to provide insights about sediment connectivity (Rodrigo‐Comino and Cerdà, ).…”
Section: Introductionmentioning
confidence: 97%
“…To assess changes in soil level, stock unearthing method (SUM) has been a useful method because: i) it is relatively easy to be applied; ii) it generates accurate data which are representative of longterm periods of soil erosion rates; and, iii) it is an easily reproducible tool which can generate the production of a very high actual DEM resolution (cm) without drones or planes. The papers published by Brenot et al (2006Brenot et al ( ,2008, Casalí et al (2009), Paroissien et al (2010, Chevigny et al (2014) and Quiquerez et al (2014) as well as the most recent by Rodrigo-Comino et al (2016b) and Biddoccu et al (2017) have not only provided estimates of soil erosion rates and identified the main factors responsible for intra-plot variability, but have generated new information for the education of the stakeholders about the environmental issues.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent studies have tested the SUM accuracy by comparing SUM results with digital elevation models, GPS, orthophotography (Biddoccu et al, 2017;Chevigny et al, 2014;Quiquerez et al, 2014) or with data generated from sediment collectors (Rodrigo-Comino et al, 2016b). However, all of these studies assumed the main limitation of this method: the surface between the vines (inter-row) remains planar.…”
Section: Introductionmentioning
confidence: 99%